Victor Sonna, 152 - Sonna, Victor 1977- (Van Abbemuseum, 2020)
In 2015 in New Orleans, Victor purchased the chains of an enslaved person. The number 152 was engraved on the chains. This purchase marked the start of a personal journey of discovery through Ghana and Suriname, among others. The result is an exhibition featuring one hundred and fifty two unique pieces of art - the series 152 - six films and fifty two prints in which Victor treats the subject of slavery in his own unique way. The exhibition title is a play on the number 152. A single five is added: one of the first transatlantic transports of enslaved people took place in 1525. 00For his series 152, Victor Sonna collected 152 European Gobelin tapestries created between the 18th and 20th centuries. He incorporates these in three series, entitled Bleach and cloth, Sugar and rubber and Maps, by combining them with Kente fabrics (traditional woven cloth from Ghana), African sculptures and slavery-related objects that he collected on his travels through the Netherlands, Ghana and Suriname. In a spectacular 25-metre high installation, the artworks are for the most part displayed in such a way that enables visitors to view them from both sides. As Victor Sonna himself says: "There is always more than one side to a story." The design behind the scaffolding in the museum tower is a reference to the Tower of Babel: the origin myth about the scattering of humanity into different peoples. Exhibition: Van Abbemuseum, Eindhoven, The Netherlands (18.07.2020 - 30.05.2021)
Colofon: Deze publicatie verschijnt naar aanleiding van de tentoonstelling "Victor Sonna. 152", Van Abbemuseum, Eindhoven, 18/07/2020 - 30/05/2021
Keywords: Sonna, Victor -- 1977-; Geschichte 2015; Sklaverei -- Motiv; Videokunst; Installation -- Kunst; Ausstellungskatalog -- Stedelijk Van Abbe-Museum -- 18.07.2020-30.05.2021 -- Eindhoven; Bildband